Aortoesophageal fistula in a child - Shasanka Shekhar Panda; Sandeep Agarwala; Sushil Kumar Kabra; Ruma Ray; Nidhi Sugandhi; Abdus Sami Bhat; Rakesh Lodha; Prashant Joshi; Akshay Kumar Bisoi; Arundeep Arora; Arun Kumar Gupta (Wolters Kluwer Medknow Publications, 2013)
Aortoesophageal fistulae (AEF) are rare and are associated with very high mortality. Foreign body ingestions remain the commonest cause of AEF seen in children. However in a clinical setting of tuberculosis and massive upper GI bleed, an AEF secondary to tuberculosis should be kept in mind. An early strong clinical suspicion with good quality imaging and endoscopic evaluation and timely aggressive surgical intervention helps offer the best possible management for this life threatening disorder. Our case is a 10-year-old boy who presented to the pediatric emergency with massive bouts of haemetemesis and was investigated and managed by multidisciplinary team effort in the emergency setting.